Synthesis methods to prepare single- and multi-core iron oxide nanoparticles for biomedical applications1. Issue 7 (21st February 2015) - Gutiérrez, L.; Costo, R.; Grüttner, C.; Westphal, F.; Gehrke, N.; Heinke, D.; Fornara, A.; Pankhurst, Q. A.; Johansson, C.; Veintemillas-Verdaguer, S.; Morales, M. P.
<x xml:space="preserve">Abstract</x> We review and classify synthetic routes to either single-core or multi-core iron oxide nanoparticles for biomedical applications.